2018
DOI: 10.1016/j.athoracsur.2017.07.047
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Deployment Aortic Valve Replacement: Excellent Results and Increased Effective Orifice Areas

Abstract: RDAVR facilitates reduced aortic cross-clamp and cardiopulmonary bypass times compared with standard AVR, particularly in patients undergoing concomitant procedures, allowing the use of larger prostheses and resulting in lower transvalvular gradients and higher indexed effective orifice area compared with standard AVR. Therefore, RDAVR may help to overcome patient-prosthesis mismatch in some patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 23 publications
3
50
1
Order By: Relevance
“…Surgical aortic valve replacement (SAVR) reduces mortality, provides symptom relief and increases quality of life at subsequent follow-up [1] . Furthermore, continuous improvements in SAVR techniques and new technologies have recently been developed to facilitate the procedure and reduce operative times [2] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical aortic valve replacement (SAVR) reduces mortality, provides symptom relief and increases quality of life at subsequent follow-up [1] . Furthermore, continuous improvements in SAVR techniques and new technologies have recently been developed to facilitate the procedure and reduce operative times [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have provided insight into changes in patient demographics, risk factors and outcomes of SAVR [2] . Therefore, it is necessary to study changes in practice over time and to establish outcomes after SAVR to help inform decision making for high-risk patients [3] .…”
Section: Introductionmentioning
confidence: 99%
“…27 Furthermore, the excellent post-procedural PGs of the IEV might be the result of slightly oversized valves between two sizes. 28 In consequence, the balloon expansion of an oversized valve can provoke the need of a permanent pacemaker implantation after surgery due to an atrioventricular conduction disturbance. Another potential explanation for the comparable lower post-procedural PGs is the theory that adequately positioned frame with the added skirt of the IEV might keep the outflow tract "open" leading to less turbulence.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with conventional bioprosthetic valves, where pledged-armed sutures are used to tie the valve in the right position and potentially a smaller valve is chosen, RDAV has shown superior hemodynamic characteristics so far. 28,29 Higher transvalvular PGs are usually seen as surrogate parameters for prosthesis-patient mismatch (PPM) independent from the EOA. In our study, the S3V showed higher transvalvular PGs compared with the IEV despite the fact that the transcatheter valve does not have a suture ring, which would decrease the EOA of any prosthetic valve.…”
Section: Discussionmentioning
confidence: 99%
“…Data published on the comparison between RD-AVR and SAVR underline the benefits of RD-AVR in terms of operative time reduction, CBP duration and increased effective orifice area and consequent lower postoperative transvalvular gradient [19] . The most common complications reported in the case of RD-AVR are higher incidence of pacemaker implantation, postoperative stroke and residual aortic regurgitation [20] , while the most common complications reported in the case of standard procedure tend to be exclusively surgery related as major bleeding or acute renal failure [21] .…”
Section: Discussionmentioning
confidence: 99%